Prognostic value of interferon-γ release assays, a population-based study from a TB low-incidence country. Issue 7 (30th March 2016) - Hermansen, Thomas Stig; Lillebaek, Troels; Langholz Kristensen, Kristina; Andersen, Peter H; Ravn, Pernille
Abstract : Background: The ability of interferon-γ release assays to predict the development of TB has been investigated in many studies, but few cases develop TB during follow-up limiting the generalisation of results. Methods: We assessed QuantiFERON-TB Gold In-Tube test (QFT) results from 15 980 Danish individuals and data on all TB cases in Denmark from 2005 to 2012 and determined the predictive value of the QFT for coprevalent TB (0–90 days after testing) and incident TB (>90 days). Results: Coprevalent TB was diagnosed in 10.7% (183/1703) and 0.3% (38/13 463) cases with a positive and negative QFT, respectively. For the QFT-positive cases, coprevalent TB was more frequent among persons <35 years compared with those >35  years (19.3% vs 7.2%, p<0.001). The cohort was followed-up for 52 807 person-years, median follow-up time was 3.36 years. For incident TB, the positive and negative predictive values (PPV and NPV) were 1.32% and 99.85%, respectively. Incidence rates (IR) for incident TB among QFT-positives and QFT-negatives were 383 per 10 5 and 45 per 10 5 person-years, respectively. Among cases with a positive QFT, IR for incident TB was associated with time interval since QFT (<2 years, p<0.001), but not with age (<35 years, p=0.087). Conclusions: We confirmed a high NPV of the QFT and found positive QFT associated with a higher risk of subsequent incident TB. Overall, the PPV for incident cases was 1.32%, and development of incident TB was associated with time interval after the QFT, but not with age.